Quantitative Proteomic Analysis Reveals Changes in the Benchmark Corynebacterium pseudotuberculosis Biovar Equi Exoproteome after Passage in a Murine Host - Silva, Wanderson M.; Carvalho, Rodrigo D. De Oliveira; Dorella, Fernanda A.; Folador, Edson L.; Souza, Gustavo H. M. F.; Pimenta, Adriano M. C.; Figueiredo, Henrique C. P.; Le Loir, Yves; Silva, Artur; Azevedo, Vasco (Frontiers in Cellular and Infection Microbiology, 2017)
Corynebacterium pseudotuberculosis biovar equi is the etiologic agent of ulcerative lymphangitis. To investigate proteins that could be related to the virulence of this pathogen, we combined an experimental passage process using a murine model and high-throughput proteomics with a mass spectrometry, data-independent acquisition (LC-MSE) approach to identify and quantify the proteins released into the supernatants of strain 258_equi. To our knowledge, this approach allowed characterization of the exoproteome of a C. pseudotuberculosis equi strain for the first time. Interestingly, the recovery of this strain from infected mouse spleens induced a change in its virulence potential, and it became more virulent in a second infection challenge. Proteomic screening performed from culture supernatant of the control and recovered conditions revealed 104 proteins that were differentially expressed between the two conditions. In this context, proteomic analysis of the recovered condition detected the induction of proteins involved in bacterial pathogenesis, mainly related to iron uptake. In addition, KEGG enrichment analysis showed that ABC transporters, bacterial secretion systems and protein export pathways were significantly altered in the recovered condition. These findings show that secretion and secreted proteins are key elements in the virulence and adaptation of C. pseudotuberculosis. Collectively, bacterial pathogenesis-related proteins were identified that contribute to the processes of adherence, intracellular growth and evasion of the immune system. Moreover, this study enhances our understanding of the factors that may influence the pathogenesis of C. pseudotuberculosis.